Transport simulation of EAST long-pulse H-mode discharge with integrated modeling. (7th February 2018) - Wu, M.Q.; Li, G.Q.; Chen, J.L.; Du, H.F.; Gao, X.; Ren, Q.L.; Li, K.; Chan, Vincent; Pan, C.K.; Ding, S.Y.; Jian, X.; Zhu, X.; et al.
Abstract: In the 2017 EAST experimental campaign, a steady-state long-pulse H-mode discharge lasting longer than 100 s has been obtained using only radio frequency heating and current drive, and the confinement quality is slightly better than standard H-mode, H98y2 ~ 1.1, with stationary peaked electron temperature profiles. Integrated modeling of one long-pulse H-mode discharge in the 2016 EAST experimental campaign has been performed with equilibrium code EFIT, and transport codes TGYRO and ONETWO under integrated modeling framework OMFIT. The plasma current is fully-noninductively driven with a combination of ~2.2 MW LHW, ~0.3 MW ECH and ~1.1 MW ICRF. Time evolution of the predicted electron and ion temperature profiles through integrated modeling agree closely with that from measurements. The plasma current ( I p ~ 0.45 MA) and electron density are kept constantly. A steady-state is achieved using integrated modeling, and the bootstrap current fraction is ~28%, the RF drive current fraction is ~72%. The predicted current density profile matches the experimental one well. Analysis shows that electron cyclotron heating (ECH) makes large contribution to the plasma confinement when heating in the core region while heating in large radius does smaller improvement, also a more peaked LHW driven current profile is got when heating in the core. Linear analysis shows that the high- k modes instability (electron temperature gradient driven modes) is suppressed in the core region where exists weak electron internal transport barriers. The trapped electron modes dominates in the low- k region, which is mainly responsible for driving the electron energy flux. It is found that the ECH heating effect is very local and not the main cause to sustained the good confinement, the peaked current density profile has the most important effect on plasma confinement improvement. Transport analysis of the long-pulse H-mode experiments on EAST will be helpful to build future experiments.